Will laser Doppler vibrometry be used in facial aesthetic diagnostics? (Journal of Face Aesthetics, 2025)
Dysfunctions of the temporomandibular joint are associated with disturbances in muscle activity and joint function. It is a coupled joint, so the blockage of one joint requires excessive mobility of the other, which can significantly affect the asymmetry of the lower facial third, or on facial aesthetics. The coexistence of hypertrophy of the masticatory muscles, such as the masseter and temporal muscles, can also influence the change in facial aesthetics and dental arches. Detailed diagnostics of the masticatory system dysfunction provide the opportunity to plan and implement the most effective treatment and restore proper facial aesthetics. Doppler laser vibrometry is a method that allows for vibration measurements without direct contact with the tested object. Doppler laser vibrometry operates on the principle of the Doppler effect and uses a helium‑neon laser. This enables measurements in various fields. In the study, the PDV-100 vibrometer was used. The work presents example studies in which Doppler laser vibrometry was employed, along with a brief description of available laser vibrometers. It also presents the results obtained during the measurement of skull vibrations. Differences in vibration frequency were demonstrated in individuals with temporomandibular joint disorders compared to the control group.
Keywords: vibrations; temporomandibular joint; laser Doppler vibrometry; facial aesthetics